1992
DOI: 10.1007/bf01048783
|View full text |Cite
|
Sign up to set email alerts
|

Foliar urea fertilization of cereals: A review

Abstract: It has been suggested that there are several potential benefits of providing nitrogen to cereals via the foliage as urea solution. These include: reduced nitrogen losses through denitrification and leaching compared with nitrogen fertilizer applications to the soil; the ability to provide nitrogen when root activity is impaired e.g., in saline or dry conditions, and uptake late in the season to increase grain nitrogen concentration. Factors that influence the degree of foliar absorption in field conditions hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(120 citation statements)
references
References 40 publications
7
111
1
1
Order By: Relevance
“…These results suggest that increases in grain yield following late-season urea applications were found only when previous N applications were insufficient to obtain maximum yield (Gooding and Davies, 1992;Gooding et al, 1997). No significant response of specific weight was found in these experiments, suggesting that the lowest topdressed N rate of 100 kg ha -1 was high enough to obtain a high specific weight.…”
Section: Determination Of Yieldmentioning
confidence: 80%
See 2 more Smart Citations
“…These results suggest that increases in grain yield following late-season urea applications were found only when previous N applications were insufficient to obtain maximum yield (Gooding and Davies, 1992;Gooding et al, 1997). No significant response of specific weight was found in these experiments, suggesting that the lowest topdressed N rate of 100 kg ha -1 was high enough to obtain a high specific weight.…”
Section: Determination Of Yieldmentioning
confidence: 80%
“…To decrease these aleatory variations of yield and grain N content farmers often use higher rates of N fertilizer than those required to satisfy the demand, and as a consequence there is an increase in the risk of leaching. To reduce N losses several reports recommended applications of N to be postponed to later stages of the growing season, which favors protein build-up in the grain over yield (Sarandón and Gianibelli, 1992), and enhances the bread-making quality of the flour (Altman et al, 1983;Gooding et al, 1991;Gooding and Davies, 1992). However, the effect is a function of the crop N nutrition status and of the climate conditions, and so this effect is difficult to forecast in Mediterranean areas with high variation in climate (Lloveras et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this late-season N fertilization strategy could be more easily adapted by farmers as it does not require a dedicated passage in the field, if combined and tank mixed with a fungicide treatment, although there is a limit to how much foliar N can be applied without incurring leaf burn (Jones and Olson-Rutz, 2012;Krogmeier et al, 1989). The risk of foliage burning is higher when the N source is ammonium nitrate or ammonium sulfate rather than urea (Gooding and Davies, 1992). Moreover, foliar application needs to be avoided early in the morning when dew is still on the crop or when there are high temperatures during the day (Arnall et al, 2012;Woolfolk et al, 2002).…”
mentioning
confidence: 99%
“…Gooding and Davies (1992) suggested that benefits include reduced denitrification and leaching, improved fertilizer efficiency and reinforce the late seasonal N uptake. Tea et al (2004) demonstrated that N provided by foliar fertilization is mainly incorporated in storage proteins, which are responsible for bread-making quality.…”
mentioning
confidence: 99%